Aspects of the Aligned Magnetic Field Past a Stratified Inclined Sheet with Nonlinear Convection and Variable Thermal Conductivity - BILAL, Muhammad; INAM, Saba; KANWAL, Shamsa; NAZEER, Muzma (Engineering Transactions, 2021)
An analytical study of a two-dimensional boundary layer flow of an upper-convected Maxwell fluid is examined. In addition, an aligned magnetic field over the inclined shrinking/stretching stratified sheet in a non-Darcian porous medium is considered. The heat transfer effects are employed through nonlinear convection and variable thermal conductivity. The associated higher-order nonlinear equations are transformed to ordinary first-order differential equations by using similarity transformation. The resulting ordinary first-order differential equations are then solved numerically by the shooting method. This paper aims to investigate the special effects of parameters on velocity and temperature profiles. The results are also discussed, graphically and numerically for the skin friction and Nusselt number.